Correlation of micro-inflammatory reaction and level of omentin-1 expression with coronary heart disease in maintenance hemodialysis patients - ZHU Shi-yan; CHEN Jian-quan; LUO Cheng-zhi; LI Dan-ni; FU Ling-ling; CHEN Chang-ming; GAN Ping (Linchuang shenzangbing zazhi)
Objective To investigate the correlation between the micro-inflammatory reaction and the level of omentin-1 expression with the presence of coronary heart disease(CHD)in maintenance hemodialysis(MHD)patients.Methods Methods A total of 70 patients with MHD were admitted into our research during June 2010 to November 2016.All the patients were divided into 2groups:CHD group(group A)(n=36)and non-CHD group(group B)(n=34).The plasma levels of high sensitivity c-reactive protein(hs-CRP),interleukin-6(IL-6),omentin-1 and other clinical markers were also measured during the first 3 days.After three times of measurements with the same techniques at different time points(the first month,the third month,and the sixth month),the average values were taken as a reference.We analyzed the change of the parameters and evaluated their correlation with the CHD.Results The hs-CRP and IL-6 levels were significantly higher(P<0.05),and ALB and Hb levels were significantly lower in group A than in group B(P<0.05).The level of SCr and BUN had no statistically significant difference between two groups(P>0.05).The level of omentin-1 in the group A(12.85±6.35 ng/mL)was significantly lower than that in the group B(18.58±7.68)ng/mL(P<0.05).Pearson correlation analysis revealed that the level of omentin-1was negatively correlated with hs-CRP and IL-6(r=-0.235,P<0.05;r=-0.186,P<0.05),and positively correlated with Alb and Hb(r=0.324,P<0.05;r=0.296,P<0.05),but not correlated with SCr and BUN(r=-0.028,P>0.05;r=-0.032,P>0.05).Logistic regression analysis showed that the increases in hs-CRP and IL-6 or the decreases in omentin-1 were the risk factors for CHD,and the Alb,Hb,SCr and BUN had no correlation with the incidence of CHD.ConclusionsThe increases in hs-CRP and IL-6 or the decrease in omentin-1 may be involved in the occurrence and development of CHD.